Imitating the effects of drilling fluid invasion on the strength behaviors of hydrate-bearing sediments: An experimental study - Pei, Jun; Wei, Na; Zhang, Boning; Zhao, Jinzhou; Kvamme, Bjørn; Coffin, Richard B.; Li, Haitao; Bai, Ruiling (Frontiers in Earth Science, 2022)
The drilling fluid invasion into hydrate-bearing sediments will change the geomechanical properties of the reservoir and may lead to uncontrolled geological disasters in the worst case. Native sediments are replaced with artificial samples in this study to investigate the effect of drilling fluid invasion on the strength behaviors of hydrate-bearing sediments. The triaxial test is used primarily to assess the strength behaviors of hydrate-bearing sediments at varying temperatures, pressures, and hydrate saturation levels. The process of water-based drilling fluid penetrating into hydrate-bearing sediments is then experimentally imitated under various experimental conditions, with reservoir temperature of 4°C and pore pressure of 10 MPa. The possible repercussions of drilling fluid invasion and hydrate phase transition are identified by testing the mechanical properties of sediments under various invasion times and temperatures. The findings reveal that when hydrate saturation rises from 5% to 35%, the gas hydrate sediments shift from strain hardening to strain softening, with the critical hydrate saturation value of transition is between 15% and 25%. Peak strength increases with increasing hydrate saturation and pressure, and decreases with increasing temperature, whether drilling fluid invasion is present or not. The peak strength, Young’s modulus, shear modulus, and secant modulus of hydrate sediments all decreased significantly after drilling fluid invasion, although the Poisson’s ratio rose. These mechanical parameters are related to temperature and pressure under the action of drilling fluid. Finally, engineering and research recommendations for reducing the risk of drilling fluid invasion and hydrate dissociation are made based on experimental findings and theoretical analysis. This study innovatively examine the geomechanical mechanical properties of drilling fluid invading hydrate reservoir, which is critical for avoiding production concerns.